Removal of Cd(II) and Pb(II) from wastewater by using triethylenetetramine functionalized grafted cellulose acetate-manganese dioxide composite. (5th September 2016) - Yakout, Amr A.; El-Sokkary, Ramadan H.; Shreadah, Mohamed A.; Abdel Hamid, Omnia G.
Highlights: Extraction of cellulose from mangrove trees ( Avicennia marina ) roots pulp. Conversion extracted cellulose to cellulose acetate composite then immobilized after grafting. The functionalized composite was successfully employed for the removal of Cd(II) and Pb(II) ions from wastewater and seawater samples. Abstract: In this manuscript, we have studied the removal of Cd(II) and Pb(II) ions from aqueous solution by using triethylenetetramine functionalized cellulose acetate grafted with the copolymer-manganese dioxide composite. The novel sorbent cellulose was extracted from the mangrove trees ( Avicennia marina ) and it was then acetylated and grafted with acrylamide. The sorbent composite was designed to interact simultaneously with higher metal loading by complexation-adsorption process. FT-IR, SEM, EDAX and TGA techniques were employed to characterize the cellulose modified composite. Sorption equilibria were established after 30 min and their data were described by Langmuir and Freundlich models. The functionalized hybrid cellulose composite showed maximum adsorption capacity 82.06 and 196.84 mg g −1 for Cd(II) and Pb(II), respectively. The studied metal ions were successfully recovered from real wastewater samples of different matrices.